Short carbon fiber reinforced low-expansion phosphate ceramic material and preparation method thereof
By introducing chopped carbon fibers into NZP group phosphate ceramic materials and using rapid hot pressing and sintering technology, the problems of low density and poor mechanical properties of existing materials are solved, and high density, excellent mechanical properties, low thermal expansion and low thermal Synergistic optimization of conductivity.
Patent Information
- Application Number
- CN202411627794.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing NZP group phosphate ceramic materials have low density and poor mechanical properties during sintering, and the introduced second phase is usually a high-expanded phase, making it difficult to maintain low thermal expansion and low thermal conductivity while increasing strength.
By introducing chopped carbon fibers into NZP group phosphate ceramic materials, uniformly dispersed by wet ball milling, mechanical stirring, ultrasonic oscillation, etc., followed by rapid hot pressing and sintering in a vacuum or argon inert atmosphere, high-quality radial production was prepared Density, excellent mechanical properties, chopped carbon fiber reinforced low-expanded phosphate ceramic material.
The high density and excellent mechanical properties of chopped carbon fiber-reinforced low-expanded phosphate ceramic materials are achieved, low thermal expansion coefficient and low thermal conductivity are maintained, and the mechanical properties are greatly improved, which are suitable for large-scale production.
Smart Images

Figure CN119462188A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic-based composite materials, and particularly relates to a chopped carbon fiber reinforced low-expansion phosphate ceramic material and a preparation method thereof. Background Art
[0002] Thermal expansion and contraction are basic properties of objects. Dimensional changes and thermal mismatch caused by temperature changes have become bottlenecks that restrict the rapid development of many research fields such as aerospace, electronic thermal management, and precision instruments. Thermally stable materials with low expansion coefficients and excellent comprehensive performance have become the key to solving the above problems.
[0003] Sodium zirconium phosphate (NaZr2(PO3)4) is referred to as NZP, in which the cation (Na + 、Zr 4+ , P 5+ ) positions can undergo a variety of different ion substitutions to form a series of derivatives with the same structure, which are collectively referred to as NZP family compounds. The NZP family phosphate ceramics prepared from the compound as powder have negative expansion or near-zero expansion, low thermal conductivity and thermal shock resistance, and have important applications and research value in nuclear waste fixation, aerospace, precision instruments, and high-temperature missiles in the military field. Although NZP family phosphate ceramic materials have a low thermal expansion coefficient, they are difficult to sinter and have a low density. Under normal circumstances, they can only reach 76.7-81.1% of the theoretical density. Therefore, their mechanical properties are poor, which seriously limits their application. Researchers have improved the mechanical strength of NZP family phosphate ceramics by adding sintering aids, silicon carbide whiskers, ion substitution, etc., but the effect is not prominent enough; in addition, the introduced second phase is usually a high expansion phase, most of which can react with NZP family phosphate ceramics, making it difficult to obtain a stable two-phase material. Therefore, how to maintain low thermal expansion and low thermal conductivity of NZP family phosphate ceramic materials while improving strength is still a research hotspot today.
[0004] Chopped carbon fibers have the advantages of low density, low thermal conductivity, and low thermal expansion coefficient. At the same time, when microcracks are generated inside the ceramic, the introduced chopped fibers can exert toughening mechanisms such as fiber debonding, pull-out, and deflection cracks, effectively inhibiting the extension of microcracks and thus improving the mechanical properties of the composite material, making it more reliable in practical applications. However, research on chopped carbon fiber reinforced low expansion phosphate ceramic materials has not been reported.
[0005] In view of the above-mentioned defects, the inventors of the present invention proposed the present invention after a long period of research and practice. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention discloses a chopped carbon fiber reinforced low expansion phosphate ceramic material and a preparation method thereof. The chopped carbon fiber reinforced low expansion phosphate ceramic material of the present invention has high density, excellent mechanical properties, and takes into account low thermal expansion coefficient and low thermal conductivity, and has good application prospects.
[0007] Furthermore, the preparation method of the chopped carbon fiber reinforced low expansion phosphate ceramic material comprises the following steps:
[0008] The first step: weighing low expansion phosphate ceramic powder and sintering aid to obtain a mixed powder, wherein the amount of the sintering aid added is 0-10wt% of the mass of the mixed powder, and the obtained mixed powder is placed in a ball mill, and wet-milled for 4-12 hours using anhydrous ethanol as a medium to obtain a uniform ceramic slurry;
[0009] Step 2: Add the chopped carbon fiber into ethanol, add a dispersant, use a stirrer to mechanically stir for 2-10 hours, and then use ultrasound to oscillate so that the agglomerated chopped carbon fiber is evenly dispersed in the ethanol to obtain an ethanol-chopped carbon fiber solution;
[0010] Step 3: Add the ceramic slurry obtained in the first step to the ethanol-chopped carbon fiber solution in the second step, continue ball milling and mixing, dry in a vacuum oven at 50-120°C for 2-10h, and obtain a low expansion phosphate ceramic mixed powder containing chopped carbon fibers after sieving;
[0011] Step 4: placing the mixed powder obtained in the third step in a graphite mold for cold pressing to obtain a pressed green body, applying a pressure of 10-60 MPa, and holding the pressure for 5-20 min;
[0012] Step 5: Place the compact obtained in the fourth step into a rapid hot pressing sintering furnace, and sinter it under the protection of a vacuum or argon inert atmosphere to obtain a chopped carbon fiber reinforced low expansion phosphate ceramic material.
[0013] Furthermore, the low expansion phosphate ceramic powder in the first step is one or more of the NZP family compounds.
[0014] Furthermore, the sintering aid in the first step is one or a combination of Al2O3, ZrO2, Y2O3, MgO, ZnO2, SiO2, TiO2, B2O3, and La2O3.
[0015] Furthermore, the diameter of the chopped carbon fiber in the second step is 7-20 μm, the length is ≤20 mm, and the amount of the chopped carbon fiber added is 0.5-50 wt % of the total mixed powder mass.
[0016] Furthermore, in the second step, the dispersant is selected from at least one of sodium carboxymethyl cellulose, polymethacrylate, tetramethyl ammonium hydroxide, polyethylene glycol, sodium polyacrylate and sodium tripolyphosphate, and the mass of the dispersant is 0.2-5wt% of the mass of the ceramic powder.
[0017] Furthermore, in the second step, the ultrasonic frequency is 20-130 kHz and the time is 5-30 min.
[0018] Furthermore, in the third step, the ball mill has a rotation speed of 100-400 r / min and a ball milling time of 30 min-4 h.
[0019] Furthermore, the conditions for the rapid hot pressing sintering in the fifth step are: sintering temperature of 1100-1400°C, heat preservation time of 5-60min, heating rate of 10-200°C / min, cooling rate of 10-150°C / min, and pressure of 5-50MPa.
[0020] Beneficial effects of the present invention:
[0021] The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof provided by the present invention have the following advantages compared with the prior art:
[0022] 1. The three-point bending strength of the short carbon fiber reinforced low expansion phosphate ceramic material prepared by the present invention reaches 134MPa, and the average thermal expansion coefficient is 0.67×10 -6 / ℃(100-800℃), thermal conductivity is 0.85W m -1 / ℃(800℃).
[0023] 2. Compared with the original phosphate ceramic material, the mechanical properties of the short-cut carbon fiber reinforced low-expansion phosphate ceramic material prepared by the present invention are greatly improved, while maintaining a low thermal expansion coefficient and low thermal conductivity, thereby achieving the coordinated optimization of the comprehensive performance of the material including mechanical properties, thermal expansion properties, and thermal conductivity.
[0024] 3. The process of the present invention is simple, the preparation process cycle is short, the cost is low, it is suitable for large-scale production, and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD spectrum of the chopped carbon fiber reinforced low expansion phosphate ceramic prepared in Example 1.
[0026] Figure 2 This is the SEM image of the chopped carbon fiber reinforced low expansion phosphate ceramic prepared in Example 1.
[0027] Figure 3 The thermal conductivity of the chopped carbon fiber reinforced low expansion phosphate ceramic prepared in Example 1.
[0028] Figure 4 This is a SEM image of the chopped carbon fiber reinforced low expansion phosphate ceramic prepared in Example 2.
[0029] Figure 5 This is the thermal expansion curve of the chopped carbon fiber reinforced low expansion phosphate ceramic prepared in Example 2. DETAILED DESCRIPTION
[0030] The technical scheme of the embodiment of the present invention will be more clearly explained below in conjunction with the drawings in the embodiment of the present invention. The following description is only a preferred embodiment of the present invention, but is not limited to the following embodiment and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0031] Example 1
[0032] A chopped carbon fiber reinforced low expansion phosphate ceramic material and a preparation method thereof, comprising the following steps:
[0033] Weigh low-expansion CaZr4(PO4)6 ceramic powder, put the powder into a ball mill, and perform wet ball milling for 4 hours using anhydrous ethanol as a medium to obtain a uniform ceramic slurry.
[0034] Short-cut carbon fibers with a diameter of 7 μm and a length of 3 mm are added to ethanol in an amount of 5 wt% of the powder mass. 0.5 wt% of polymethacrylate is added, and mechanical stirring is performed using a stirrer for 3 hours. Ultrasonic oscillation is then performed with an ultrasonic frequency of 20 kHz for 10 minutes to uniformly disperse the agglomerated short-cut carbon fibers in ethanol to obtain an ethanol-chopped carbon fiber solution.
[0035] The obtained ceramic slurry was added to the ethanol-chopped carbon fiber solution and ball milling was continued at a rotation speed of 200 r / min for 30 min. It was then dried in a vacuum oven at 80°C for 2 h and passed through an 80-mesh sieve to obtain a low-expansion phosphate ceramic mixed powder containing chopped carbon fibers.
[0036] The mixed powder is placed in a graphite mold and cold pressed to obtain a compact. The pressure is 20 MPa and the holding time is 10 min.
[0037] The compact was placed in a rapid hot pressing sintering furnace and sintered in vacuum at a sintering temperature of 1200°C for 10 minutes at a heating rate of 100°C / min, a cooling rate of 50°C / min, and a pressure of 40MPa to obtain the short carbon fiber reinforced low expansion phosphate ceramic material. The XRD spectrum of the short carbon fiber reinforced low expansion phosphate ceramic material obtained in Example 1 is as follows: Figure 1As shown; SEM pictures as Figure 2 As shown; the flexural strength is 134MPa; the average thermal expansion coefficient is 0.67×10 -6 / ℃(100-800℃); thermal conductivity Figure 3 As shown, the thermal conductivity is 0.85 W m at 800 °C. -1 / ℃.
[0038] Example 2
[0039] A chopped carbon fiber reinforced low expansion phosphate ceramic material and a preparation method thereof, comprising the following steps:
[0040] Weigh low-expansion CaZr4(PO4)6 ceramic powder, put the powder into a ball mill, and perform wet ball milling for 6 hours using anhydrous ethanol as a medium to obtain a uniform ceramic slurry.
[0041] Short-cut carbon fibers with a diameter of 7 μm and a length of 3 mm are added to ethanol in an amount of 10 wt% of the powder mass. 1 wt% sodium carboxymethyl cellulose is added, and mechanical stirring is performed using a stirrer for 2 hours. Ultrasonic oscillation is then performed with an ultrasonic frequency of 50 kHz for 5 minutes to uniformly disperse the agglomerated short-cut carbon fibers in ethanol to obtain an ethanol-chopped carbon fiber solution.
[0042] The obtained ceramic slurry was added to the ethanol-chopped carbon fiber solution and ball milling was continued at a rotation speed of 100 r / min for 1 h. It was then dried in a vacuum oven at 80°C for 2 h and passed through an 80-mesh sieve to obtain a low-expansion phosphate ceramic mixed powder containing chopped carbon fibers.
[0043] The mixed powder is placed in a graphite mold and cold pressed to obtain a compact. The pressure is 10 MPa and the holding time is 20 min.
[0044] The compact was placed in a rapid hot pressing sintering furnace and sintered in vacuum at a sintering temperature of 1200°C for 12 minutes at a heating rate of 100°C / min, a cooling rate of 40°C / min, and a pressure of 40MPa to obtain the short carbon fiber reinforced low expansion phosphate ceramic material. The SEM image of the short carbon fiber reinforced low expansion phosphate ceramic material obtained in Example 2 is as follows: Figure 4 As shown; the bending strength is 84MPa; the thermal expansion curve is as shown Figure 5 As shown, the average thermal expansion coefficient is 1.1×10 -6 / ℃(100-800℃); thermal conductivity at 800℃ is 0.61W m -1 / ℃.
[0045] Example 3
[0046] A chopped carbon fiber reinforced low expansion phosphate ceramic material and a preparation method thereof, comprising the following steps:
[0047] Weigh low-expansion BaZr4(PO4)6 ceramic powder and ZnO2 sintering aid, with the amount of sintering aid added being 5wt% of the mass of the mixed powder. Put the mixed powder into a ball mill and perform wet ball milling for 6 hours using anhydrous ethanol as the medium to obtain a uniform ceramic slurry.
[0048] Short-cut carbon fibers with a diameter of 5 μm and a length of 7 mm are added to ethanol in an amount of 20 wt% of the powder mass. 1 wt% sodium carboxymethyl cellulose is added, and mechanical stirring is performed using a stirrer for 2 hours. Ultrasonic oscillation is then performed with an ultrasonic frequency of 60 kHz for 15 minutes to uniformly disperse the agglomerated short-cut carbon fibers in ethanol to obtain an ethanol-chopped carbon fiber solution.
[0049] The obtained ceramic slurry was added to the ethanol-chopped carbon fiber solution and ball milling was continued at a rotation speed of 100 r / min for 2 h. It was then dried in a vacuum oven at 80° C. for 2 h and passed through an 80-mesh sieve to obtain a low-expansion phosphate ceramic mixed powder containing chopped carbon fibers.
[0050] The mixed powder is placed in a graphite mold and cold pressed to obtain a compact. The pressure is 30 MPa and the holding time is 5 minutes.
[0051] The compact is placed in a rapid hot pressing sintering furnace and sintered in vacuum at a sintering temperature of 1300°C, a heat preservation time of 8 minutes, a heating rate of 80°C / min, a cooling rate of 100°C / min, and a pressure of 50MPa to obtain the chopped carbon fiber reinforced low expansion phosphate ceramic material.
Claims
1. A chopped carbon fiber reinforced low expansion phosphate ceramic material and a preparation method thereof, characterized in that: The preparation method comprises the following steps: The first step: weighing low expansion phosphate ceramic powder and sintering aid to obtain a mixed powder, wherein the amount of the sintering aid added is 0-10wt% of the mass of the mixed powder, and the obtained mixed powder is placed in a ball mill, and wet-milled for 4-12 hours using anhydrous ethanol as a medium to obtain a uniform ceramic slurry; Step 2: Add the chopped carbon fiber into ethanol, add a dispersant, use a stirrer to mechanically stir for 2-10 hours, and then use ultrasound to oscillate so that the agglomerated chopped carbon fiber is evenly dispersed in the ethanol to obtain an ethanol-chopped carbon fiber solution; Step 3: Add the ceramic slurry obtained in the first step to the ethanol-chopped carbon fiber solution in the second step, continue ball milling and mixing, dry in a vacuum oven at 50-120°C for 2-10h, and obtain a low expansion phosphate ceramic mixed powder containing chopped carbon fibers after sieving; Step 4: placing the mixed powder obtained in the third step in a graphite mold for cold pressing to obtain a pressed green body, applying a pressure of 10-60 MPa, and holding the pressure for 5-20 min; Step 5: Place the compact obtained in the fourth step into a rapid hot pressing sintering furnace, and sinter it under the protection of a vacuum or argon inert atmosphere to obtain a chopped carbon fiber reinforced low expansion phosphate ceramic material.
2. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: In the first step, the low expansion phosphate ceramic powder is one or more of the NZP family compounds.
3. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: In the first step, the sintering aid is one or a combination of Al2O3, ZrO2, Y2O3, MgO, ZnO2, SiO2, TiO2, B2O3, and La2O3.
4. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: The diameter of the chopped carbon fiber in the second step is 7-20 μm, the length is ≤20 mm, and the amount of the chopped carbon fiber added is 0.5-50 wt % of the total mixed powder mass.
5. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: In the second step, the dispersant is selected from at least one of sodium carboxymethyl cellulose, polymethacrylate, tetramethyl ammonium hydroxide, polyethylene glycol, sodium polyacrylate and sodium tripolyphosphate, and the mass of the dispersant is 0.2-5wt% of the mass of the ceramic powder.
6. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: The ultrasonic frequency in the second step is 20-130 kHz, and the time is 5-30 min.
7. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: In the third step, the ball mill has a rotation speed of 100-300 r / min and a ball milling time of 30 min-4 h.
8. The chopped carbon fiber reinforced low expansion phosphate ceramic material and the preparation method thereof according to claim 1, characterized in that: The conditions of the rapid hot pressing sintering in the fifth step are: sintering temperature of 1000-1400°C, heat preservation time of 5-60min, heating rate of 10-200°C / min, cooling rate of 10-150°C / min, and pressure of 5-50MPa.
9. A chopped carbon fiber reinforced low expansion phosphate ceramic material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Carbon fiber reinforced phosphate composite material forming process
CN102424574A
Preparation method of NZP family ceramic material with continuously adjustable thermal expansion coefficient
CN108164262A
Chopped carbon fiber reinforced phosphoric acid-based geopolymer composite material and preparation method thereof
CN113831101A
Carbon-fiber reinforced ceramic composite material
JP1999092244A